Green Synthesis and Characterization of ZnO Nanoparticles from Cynoglossum microglochin Extract with Broad Spectrum Antioxidant, Antileishmanial, Antibacterial and Anticancer Activities - Beenish Kalsoom; Ishtiaq Hassan; Abdul Basit; Ikram Ullah; Muhammad Tariq; Manan Khan; Inam Ullah (Journal of Pharmaceutical Innovation, 2027)

Regulatory roles of miRNAs in development and progression of Hepatocellular carcinoma - Yasmeen Ishaq; Bisma Rauff; Muhammad Rehan Chaudhry; Mohamad S. Hakim; Sana Khurshid; Shafiq Ahmad Chudhary; Aqsa Ikram (Molecular Biology Reports, 2026)

From cratonic interiors to deltaic shores: Tectonic and paleoclimatic influences on the diagenetic evolution of Khewra Sandstone, Salt Range, Pakistan - Muhammad Ajaz Abbasi; Imran Khan; Atif Iqbal Abbasi; Muhammad Jamil; Nawaz Ikram; Syed Ahsan Hussain Gardezi; Zulfiqar Haider Awan; Umair Aftab Choudary; Abdul Wali Khan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Groundwater Contamination and Probabilistic Health Risk Assessment of Heavy Metals in Coal Mining Areas of Punjab, Pakistan - Aima Iram Batool; Muhammad FayyazUrRehman; Naima Huma Naveed; Javaria Ikram; Hakim Bibi (Water, Air, & Soil Pollution, 2026)

Exploring the potential of green nanomaterials: An ecofriendly approach for sustainable agriculture, food safety and environmental pollution control - Muhammad Ikram; Rui Xu; Yemin Guo; Xia Sun; Du Fangling; Nortoji A. Khujamshukurov (Food Research International, 2026)

Lactiplantibacillus plantarum AS21 Reduces Colitis in Mice by Modulating Inflammation, Gut Barrier Function, and Microbiota in an Intervention Dose and Time-dependent Manner - Ali Sher Bacha; Mengyan Chen; Zitong Ding; Mengya Jia; Hu Chen; Ikram Khan; Muhammad Ishaq; Azmat Ullah Jan; Ashiq Khan; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Correction to: Climate‐driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Retraction Note: Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus - Ikram Ullah; Haroon Badshah; Muhammad Imran Naseer; Hae Young Lee; Myeong Ok Kim (NeuroMolecular Medicine, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Establishment of callus culture, elicitation study, and NMR-based metabolomics of Artemisia vulgaris L. - Ali Muhammad Zakariya; Nur Kusaira Khairul Ikram; Dwi Kusuma Wahyuni; Mohd Zuwairi Saiman (In Vitro Cellular & Developmental Biology - Plant, 2026)
Artemisia vulgaris L. has attracted considerable interest for its pharmaceutical, agricultural, and cosmetic applications due to its rich bioactive metabolites. However, low metabolite yields and challenges in large-scale cultivation constrain its commercial potential. Therefore, this study aimed to optimize a callus regeneration system, develop a comprehensive metabolite profile of the callus culture, and assess the effects of elicitor treatments on metabolite biosynthesis pathways to identify optimal concentrations for enhanced metabolite production. In vitro callus cultures were initiated on Murashige and Skoog (MS) medium with varying levels of benzylaminopurine (BAP), α-naphthaleneacetic acid (NAA), and 2,4-dichlorophenoxyacetic acid (2,4-D) phytohormones. Callus cultures were evaluated for colour, texture, moisture content, and biomass, and metabolite profiling was conducted using nuclear magnetic resonance (NMR) platform. Elicitor treatments of the callus cultures with different concentrations of methyl jasmonate (MJ) and salicylic acid (SA) were analysed via NMR-based metabolomics. MS medium containing 2.0 mg L⁻ 1 BAP and 0.2 mg L⁻ 1 NAA was optimal for callus culture establishment and maintenance. A total of eighteen compounds were identified, including dihydroartemisinic acid, caffeic acid, and gallic acid. MJ and SA functioned as stress elicitors, modulating the tricarboxylic acid cycle, phenylpropanoid, and artemisinin biosynthesis pathways, although they had limited direct effects on artemisinin concentrations. Overall, this study optimized callus culture production, generated the first detailed metabolite profile, and highlighted the potential of elicitation strategies to enhance bioactive metabolite yields, providing a foundation for future metabolic engineering and industrial applications.

How decentralized blue-green-grey infrastructure reshapes urban drainage performance: A cost-reliability-resilience optimization framework - Mo Wang; Yijia Zhang; Chuanhao Sun; Rana Muhammad Adnan Ikram; Kexin Liu (Journal of Environmental Management, 2026)

Silicon seed inoculation enhances antioxidant defenses, physio-biochemical mechanisms and yield traits in maize hybrids under heat stress conditions at vegetative and tasseling stages - Ijaz Hussain; M. Habib Ur-Rahman; Rao Muhammad Ikram; Muhammad Baqir Hussain; Saeed Ahmad; Reimund P. Roetter (Field Crops Research, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Vitamin D Promotes Neuronal Survival via Nrf2 Upregulation in D-Galactose–Induced Mice: An In-Vivo and In-Silico Study - Fawad Ali Shah; Muhammad Zakria; Faten F. Bin Dayel; Najeeb Ur Rehman; Sarwat Jahan; Muhammad Ikram (Journal of Neuroimmune Pharmacology, 2026)

Correction: Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2026)

Deciphering the synergy of eudragit and polyethylene glycol supported cobalt oxide for catalytic, electrocatalytic and antibacterial activity: Computational insights - Atika; Muhammad Imran; Iram Shahzadi; Ali Haider; Sumaira Rasool; Anwar Ul-Hamid; Norah A. Albassami; Muhammad Ikram (Journal of Water Process Engineering, 2026)

Developmental Toxicity of Lead and Copper in Chick Embryos: Morphometric and Histological Assessment of In Ovo Exposure - Aima Iram Batool; Noor Fatima; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Javaria Ikram; Iram Inayat (Biological Trace Element Research, 2026)

First principles investigation of hafnium-based perovskite hydrides XHfH3 (X: Li, Na, K, and Rb) for hydrogen storage applications - Abdellah Hammad; Djamel Bezzerga; Fouad Keramsi; Ikram Djebablia; Muhammad Zaman; Mamoun Fellah; El-Abed Haidar (Fuel, 2026)

Role of rituximab in treatment of patients with primary central nervous system lymphoma: An updated systematic review and meta-analysis - Kumail Mustafa Ali; Muhammad Farhan Ashraf; Zain Ul Abideen; Armish Rehman; Rumman Javed; Ayena Ghulam Mujtaba; Touba Diwan; Ukasha Khalid; Laiba Ikram (Acta Neurologica Belgica, 2026)

Host–Microbiota Metabolic Interactions in Atherosclerosis: Oral, gut, and Blood Perspectives - Ikram Khan; Muhammad Irfan; Ali Sher Bacha; Imran Khan; Yasir Ali; Zhiqiang Li (Probiotics and Antimicrobial Proteins, 2026)

Dual-sided Pd functionalization of groove-textured CeO2 hollow microcages boosts room temperature NO2 sensing - Yan Tong; Pengkai Xing; Wenbo Ruan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Muhammad Ikram; Xue Bai; Qin Guo; Keying Shi (Chemical Engineering Journal, 2026)

Decoding rhizosphere microbiome assembly: a dual framework of environment-driven and host genetics-driven components for sustainable agriculture - Muhammad Ikram; Burhan Khalid; Kamran Haider; Maria Batool; Maaz Ullah; Muhammad Akif; Tao Deng; Jie Kuai; Zhenghua Xu; Jie Zhao; Jing Wang; Bo Wang; et al. (Plant and Soil, 2026)

Decoding core molecular mechanisms of heat-stress tolerance in Brassica napus using transcriptomics and machine learning - Muhammad Ikram; Muhammad Farhan; Behnam Derakhshani; Sunjeet Kumar; Aliya Ayaz; Naveed Khan; Enerand Mackon; Babar Usman; Si Chengcheng; Pingwu Liu (Plant Cell Reports, 2026)

Fecal microbiota transplantation in inflammatory bowel disease: a systematic review and meta-analysis of randomized controlled trials (2020–2025) - Sania Ikram; Muneeb Ullah; Juho Lee; Nurhasni Hasan; Jin-Wook Yoo; Raees Khan; Muhammad Naeem (Inflammopharmacology, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Climate-driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Black carbon and its relationship with PM2.5 and NO2 in a high-traffic urban environment of Kuala Lumpur - Murnira Othman; Mohd Talib Latif; Haris Hafizal Abd. Hamid; Ethel Garcia; Muhammad Ikram A. Wahab; Santhyami Santhyami; Li Li (Urban Climate, 2026)

Radiative magneto-thermal modeling of tri hybrid nanofluid in blood: A Biomedical intelligent framework for hyperthermia cancer therapy - Zeeshan Ikram Butt; Iftikhar Ahmad; Muhammad Asif Zahoor Raja; Muhammad Shoaib (Journal of Thermal Biology, 2026)

Converting green into good: Pathways from green building practices to social well-being - Zulkaif Ahmed Saqib; Muhammad Ikram; Daniel Berg (Journal of Environmental Management, 2026)

In-situ sequential topotactic transformation of ZIF-8 to N-doped Zn-oxide/sulfide with defect engineering for efficient radiocesium capture - Muhammad Ikram; Toshio Yamaguchi; Iltaf Muhammad; Qirui Wang; Hongyan Liu; Shahzad Afzal; Israr Masood ul Hasan; Yongquan Zhou (Chemical Engineering Journal, 2026)

Mining of genes and pathways associated with endoplasmic reticulum stress in Brassica campestris via RNA-Seq - Aliya Ayaz; Jianjun Wang; Muhammad Ikram; Abdul Jalal; Chunmei Hu; Ying Li; Xilin Hou (Plant Cell Reports, 2026)

Precision Rewiring of Stress-Responsive Gene Networks Via CRISPR: Mechanistic Pathways Toward Climate-Smart Agriculture - Burhan Khalid; Muhammad Umer Javed; Muhammad Ikram; Muhammad Ateeq; Muhammad Atiq Ashraf; Talha Riaz; Shumaila Nawaz; Rizwan Maqbool (Journal of Crop Health, 2026)

Cow, Buffalo and Goat Milk as a Pathway for Heavy Metal Exposure from Coal Mining Activities with Spatial and Species-Specific Health Risk Evaluation - Aima Iram Batool; Muhammad FayyazUrRehman; Javaria Ikram; Naima Huma Naveed; Hakim Bibi (Biological Trace Element Research, 2026)

Carbon-based materials for photocatalytic degradation of pharmaceuticals and drugs - Shan Arif; Sufian Rasheed; Naseer Ahmad; Muhammad Ikram Nabeel; Waqas Ahmad; Thamer Alomayri; Dilshad Hussain; Syed Ghulam Musharraf (Journal of Water Process Engineering, 2026)

Ambroxol’s Role in PTZ-Induced Anxiety-Like Conditions in Mice: Targeting Neuroinflammation and Oxidative Stress via In Vivo and In Silico Approaches - Hafeeza Zafar Ali; Sarwat Jahan; Laila Ilahi; Sami Siraj; Muhammad Zakria; Najeeb Ullah; Muhammad Ikram; Ashraf Ullah Khan; Manzoor Khan; Fawad Ali Shah; Hafsah Muhammad (Molecular Neurobiology, 2026)

In-silico genome-wide identification of ADF gene family in Brassica napus under long-term high-temperature stress - Enerand Mackon; Shanshan Zhang; Zhuyu Pan; Muhammad Ikram; Latif Ullah Khan; Wajid Saeed; Muhammad Waseem; Yun Li; Pingwu Liu (Genetic Resources and Crop Evolution, 2026)

Metal organic frameworks derived novel metal sulfide (KCoZnS) nanosheet as an efficient collector for cesium ions - Muhammad Ikram; Hongyan Liu; Iltaf Muhammad; Qirui Wang; Shahzad Afzal; Masood Ul Hasan Israr; Asad Ali; Yongquan Zhou (Journal of Environmental Chemical Engineering, 2025)

Application of novel deep learning model for high-frequency water quality prediction in multi-station river networks - Yuchen Wang; Jing-Cheng Han; Yang Zhou; Xiuquan Wang; Rana Muhammad Adnan Ikram; Xu Zhao; Yuefei Huang (Journal of Environmental Chemical Engineering, 2025)

Heat stress-induced sterility in oilseed crops: a focus on Brassica napus - Muhammad Zeeshan Mola Bakhsh; Muhammad Ikram; Ahmad Ali; Haseeb ur Rehman (Molecular Biology Reports, 2025)

Cutting edge: ferroptosis in metabolic dysfunction-associated steatotic liver disease (MASLD) pathogenesis and therapy - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Teeba Ammar Rashid; Muhammad Ikram Ullah; Subasini Uthirapathy; Subbulakshmi Ganesan; Abhayveer Singh; Anita Devi; Kamal Kant Joshi; Ahmed Salman Jasim; Abed J. Kadhim (Functional & Integrative Genomics, 2025)

Liquid biopsy in breast cancer: clinical implications of ctDNA and CTCs in diagnosis, treatment and monitoring - Muhammad Umer Khan; Arooj Khawar; Muhammad Ikram Ullah; Muhammad Adnan Shan; Luca Falzone; Massimo Libra; Graziana Spoto; Javad Sharifi-Rad; Daniela Calina (Molecular and Cellular Biochemistry, 2025)

Toxic metal bioaccumulation and health-risk profiling in buffalo milk: a case study from coal mining areas of Chakwal, Pakistan - Aima Iram Batool; Javaria Ikram; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Ifrah Zafar; Hakim Bibi (Environmental Geochemistry and Health, 2025)

Biofloc systems as a sustainable strategy to minimize heavy metal bioaccumulation in aquaculture - Ruhma Ihsan; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Syed Sikandar Habib (Aquaculture International, 2025)

Synergistic effects of zinc ferrite nanoparticles and plant growth promoting rhizobacteria in alleviating lead toxicity in Mungbean - Muhammad Nafees; Ikram Khan; Sami Ullah; Iftikhar Ahmed (Folia Microbiologica, 2025)

Target Mining in Insect Genomes: Omics-Guided Innovations for Smart Pesticides - Muhammad Faizan Khurram; Maryam Tahira; Abdul Rauf; Burhan Khalid; Muhammad Ikram (Journal of Crop Health, 2025)

Therapeutic innovations: targeting ROS production in AML with natural and synthetic compounds - Mohammed Hashim Mohammed; Raed Fanoukh Aboqader Al-Aouadi; Subasini Uthirapathy; Gaurav Sanghvi; Rekha M M; Resan Shakir Abdulamer; G. V. Siva Prasad; Mayank Kundlas; Fayzulla Khamraev; Muhammad Ikram Ullah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Correction: Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

Environmental factors attributed on dissemination of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) through PM2.5 and PM10 - Nurul Tasha Zulkifle; Muhammad Ikram A Wahab; Hui-min Neoh; Siti Shahara Zulfakar (Aerobiologia, 2025)

Enhanced electrocatalytic OER performance of Ba/CS-CoFe2O4 ternary heterostructure catalyst: Experimental and theoretical insights - Qirat Yameen; Muhammad Ikram; Sawaira Moeen; Muhammad Imran; Anwar Ul-Hamid; Ghafar Ali; Souraya Goumri-Said; Mohammed Benali Kanoun (Chemosphere, 2025)

Suppression of common scab disease in potato via application of antagonistic Trichoderma harzianum and Bacillus subtilis - Ihtisham Ul Haq; Mamoona Munir; Saira Qadir; Mushtaq Ahmad; Ayesha Ikram; Muhammad Asif; Zahid Mukhtar; Fathia Mubeen; Muhammad Akhtar; Ijaz Ahmed Qureshi (Journal of Plant Diseases and Protection, 2025)

Synergistic performance of silver/polyacrylic acid doped ZrO2 nanostructures for dye degradation and bactericidal behavior with molecular docking analysis - Muhammad Ikram; Alvina Rafiq Butt; Sidra Bano; Sadia Naz; Sawaira Moeen; Anwar Ul-Hamid; Ali Haider; Amel Ayari-Akkari (Environment, Development and Sustainability, 2025)

Spectrum of BRCA1/2 pathogenic variants in Southern and Western Asia-a systematic review - Samra Khan; Ikram A. Burney; Mahrukh Nasir; Humaira Saleem; Muhammad Irfan; Muhammad Shakeel; Ishtiaq Ahmad Khan (Mutation Research - Reviews in Mutation Research, 2025)

Emodin, a Potent Anthraquinone Mitigates MPTP-Induced Parkinsons’ Disease Pathology by Regulating Nrf2 and Its Downstream Targets: In Silico and In Vivo Approach - Sarwat Jahan; Muhammad Ikram; Sami Siraj; Shakir Ullah; Muhammad Zakria; Nasir Ahmad (Molecular Neurobiology, 2025)

Cumulative effect of chronic thermal stress and glyphosate based herbicide exposure on blood parameters and cortisol levels of common carp (Cyprinus carpio) - Imran Khan; Fakhr Ul Islam; Naimat Ullah Khan; Hazrat Ali; Mohammad Attaullah; Muhammad Ikram Khan (Ecotoxicology, 2025)

Exploitation of genetic variation to enhance grain nutrient contents in bread wheat through conventional and molecular approaches - Rabia Ikram; Sania Begum; Nasr Ullah Khan; Muhammad Mohibullah; Muhammad Shakeel; Salma Shaheen; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Iram Ijaz; Muhammad Yasin (Cereal Research Communications, 2025)

Toward sustainable development: Unfolding the nexus among exports, foreign direct investment, capital formation, natural resource rent, unemployment, and low-carbon transition in Morocco - Muhammad Ikram; Rabie Nahdi (Resources Policy, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Recent advances in adsorptive removal of hazardous VOCs by metal-organic-framework-based materials - Sadia Rehman; Xianming Zheng; Muhammad Ikram Aujla; Tariq Mehmood (Chemical Engineering Journal, 2025)

The introduction of the SARS-CoV-2 BA.4 lineage into Pakistan - Zaira Rehman; Katherine Edington; Zunera Jamal; Angelika Kritz-Wilson; Gytis Dudas; Samuel Sims; Richard Myers; Babak Afrough; Leena Inamdar; Syed Adnan Haider; Aamer Ikram; Muhammad Salman; et al. (Archives of Virology, 2025)

Phytic acid content variation among wheat grain lines and its impact on nutritional quality and growth - Aurangzeb; Nodia Shujaat; Yaseen Ahmad; Muhammad Ikram; Summaira Shaheen; Muhammad Ishaq; Tahir Hameed; Saddam Hussain; Muhammad Romman; Naeem Khan (Vegetos, 2024)

Developed strategies of artificial intelligence in the prediction flow river flood using evolutionary optimized algorithms of ANN - Rana Muhammad Adnan Ikram; Mo Wang; Hossein Moayedi; Mohammad Hossein Gholizadeh; Atefeh Ahmadi Dehrashid; Quynh T. Thi (Environment, Development and Sustainability, 2024)

Identification of novel antimicrobial compounds in colostrum-associated Lactiplantibacillus plantarum ZFS 1 and 2 by integrating in vitro, machine learning and bioinformatics approaches - Zainab Fiaz; Fatima Noor; Aqsa Ikram; Talha Ali Chohan; Muhammad Zubair Aslam; Najma Arshad (Food Bioscience, 2024)

MoS2-xSex lamellae assembled with lotus-leaf-like structures for sensitive NO2 gas sensors at room temperature - Hongyi Wu; Lixue Qi; Bing Song; Yan Tong; Li Li; Muhammad Ikram; Keying Shi (Chemical Engineering Journal, 2024)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Expression analysis and characterization of morpho-physiological traits for reduced height and increased lodging resistance in barley (Hordeum vulgare L.) hybrids under different water regimes - Shoaib Liaqat; Zulfiqar Ali; Muhammad Abu Bakar Saddique; Rao Muhammad Ikram; Imtiaz Ali (Cereal Research Communications, 2024)

Flexible temperature and humidity sensors of plants for precision agriculture: Current challenges and future roadmap - Muhammad Ikram; Sikander Ameer; Fnu Kulsoom; Mazhar Sher; Ashfaq Ahmad; Azlan Zahid; Young Chang (Computers and Electronics in Agriculture, 2024)

Molybdenum amelioration of drought stress in agricultural crops: A detailed overview of mechanistic actions and future perspectives - Seyed Morteza Zahedi; Mina Marjani; Hossein Rostami Ahmadvandi; Masoumeh Alemian; Muhammad Ikram; Rahmatollah Gholami; Saadat Sarikhani; Agnieszka Ludwików; Petronia Carillo (South African Journal of Botany, 2024)

Facile synthesis of inherently nitrogen-doped PAN-derived microporous carbons activated with NaNH2 for selective CO2 adsorption and separation - Ghazanfar Nazir; Adeela Rehman; Muhammad Ikram; Muhammad Aslam; Tian C. Zhang; Awais Khalid; Sikandar Aftab; Sajjad Hussain; Hanadi A. Almukhlifi; Amal A. Abdel Hafez; Kwang Heo (Chemical Engineering Journal, 2024)

Influence of Plant Growth Promoting Rhizobacteria (PGPR) on the Growth and Yield of Sunflower (Helianthus annus L.) Under Salt Stress - Shafi Ullah; Muhammad Ikram; Samina Sarfaraz; Ijaz ul Haq; Atika Khan; Zaryab Murad; Fazal Munsif (Journal of Crop Health, 2024)

Citrus rootstocks physiological and anatomical response to heat stress - Sami Ur Rehman; Waqar Shafqat; Sufian Ikram; Waqas Shafqat Chattha; Rabia Amen; Honghong Deng; Muhammad Fasih Khalid; Muhammad Jafar Jaskani (Acta Physiologiae Plantarum, 2024)

Triethylammonium Salts of Dicoumarol: Synthesis, Characterization, Human Antiglioblastoma, Antimicrobial and Antioxidant Studies - Sadia Rehman; Muhammad Ikram; Afzal Khan; Adnan Khan; Farzia; Rizwan Khan; Mutasem Omar Sinnokrot; Vinay K. Puduvalli; Ayub Jadoon (Cell Biochemistry and Biophysics, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Assessing Soil Water and Nitrogen Movement Using EU-Rotate_N Model for Greenhouse Tomato Cultivation in the Region with Shallow Water Table - Ikram Ullah; Zhuangzhuang Cao; Xu Xiangying; Yudan Wang; Muhammad Saif Ullah; Aitazaz Ahsan Farooque; Minmin Miao (Journal of Soil Science and Plant Nutrition, 2024)

Retraction Note: Gintonin Mitigates MPTP-Induced Loss of Nigrostriatal Dopaminergic Neurons and Accumulation of α-Synuclein via the Nrf2/HO-1 Pathway - Min Gi Jo; Muhammad Ikram; Myeung Hoon Jo; Lang Yoo; Kwang Chul Chung; Seung-Yeol Nah; Hongik Hwang; Hyewhon Rhim; Myeong Ok Kim (Molecular Neurobiology, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

The concentration of particulate matters in mechanically ventilated school classroom during haze episode in Kuala Lumpur City Centre - Azwani Alias; Mohd Shahrul Mohd Nadzir; Mohd Talib Latif; Md Firoz Khan; Haris Hafizal Abd Hamid; Mazrura Sahani; Muhammad Ikram A. Wahab; Murnira Othman; Faizal Mohamed; Noorlin Mohamad; Norhaniza Amil; Otuyo Muhsin Kolapo (Air Quality, Atmosphere & Health, 2024)

Integrating FinTech with Industry 4.0 for sustainable mineral resource management: Exploring the interplay of technology, regulation, and economic dynamics - Imran Khan; Inayat Khan; Rana Muhammad Adnan Ikram; Mohammad Ajmal Ali (Resources Policy, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Current state, strategies, and perspectives in enhancing artemisinin production - Ali Muhammad Zakariya; Mohd Zuwairi Saiman; Henrik Toft Simonsen; Nur Kusaira Khairul Ikram (Phytochemistry Reviews, 2024)

Serum and salivary Cu/Zn ratio as a diagnostic biomarker for oral submucosal fibrosis: an analysis of trace metals and LOX gene variants - Rafia Shah; Feriha Fatima Khidri; Yar Muhammad Waryah; Roohi Nigar; Amber Mahmood; Hina Shaikh; Muhammad Qasim Awan; Ikram Din Ujjan; Ali Muhammad Waryah (BioMetals, 2024)

2D MXenes and their composites; design, synthesis, and environmental sensing applications - Naseer Ahmad; Sufian Rasheed; Abrar Mohyuddin; Batool Fatima; Muhammad Ikram Nabeel; Muhammad Tariq Riaz; Muhammad Najam-ul-Haq; Dilshad Hussain (Chemosphere, 2024)

Matrix scenario-based urban flooding damage prediction via convolutional neural network - Haojun Yuan; Mo Wang; Jianjun Li; Dongqing Zhang; Rana Muhammad Adnan Ikram; Jin Su; Shiqi Zhou; Yuankai Wang; Qifei Zhang (Journal of Environmental Management, 2024)

The application of multi-attribute decision making methods in integrated watershed management - Rana Muhammad Adnan Ikram; Sarita Gajbhiye Meshram; Mohd Abul Hasan; Xinyi Cao; Ehsan Alvandi; Chandrashekhar Meshram; Saiful Islam (Stochastic Environmental Research and Risk Assessment, 2024)

Synergized toxicity exhibited by indigenous entomopathogenic fungal strains, plant extracts and synthetic insecticides against fall armyworm Spodoptera frugiperda (J.E. Smith) under laboratory and semi-field conditions - Kanwer Shahzad Ahmed; Muhammad Zeeshan Majeed; Samy Sayed; Bader Z. Albogami; Laila A. Al-Shuraym; Hina Safdar; Ikram Ul Haq; Abu Bakar Muhammad Raza (Journal of Plant Diseases and Protection, 2023)

Influence of Phosphate Solubilizing Bacteria on the Growth of mustard Grown Under Drought Stress Conditions - Farhat Suhail; Aftab Afzal; Laraib Naseer; Aneela Pervaiz; Muhammad Ikram; Summaira Shaheen; Yasir Islam; Naeem Khan (Agricultural Research, 2023)

Bibliometric analysis and literature review of occupant thermal comfort in naturally ventilated buildings (1995–2021) - Mohammed Awad Abuhussain; Badr Saad Alotaibi; Ikram Bello Suru; Yakubu Aminu Dodo; Mohammad Abdullah Alshenaifi; Muhammad Saidu Aliero (Environmental Science and Pollution Research, 2023)

Development of the artificial neural network’s swarm-based approaches predicting East Azerbaijan landslide susceptibility mapping - Yesen Sun; Hong-liang Dai; Lei Xu; Abed Asaditaleshi; Atefeh Ahmadi Dehrashid; Rana Muhammad Adnan Ikram; Hossein Moayedi; Hossein Ahmadi Dehrashid; Quynh T. Thi (Environment, Development and Sustainability, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

First report of Geotrichum candidum causing rose blight disease in Pakistan - Muhammad Talha Ikram; Muhammad Naveed Aslam; Anam Moosa; Faisal Zulfiqar; Muhammad Taimoor Shakeel; Roshaan Ahmed; Muneeb Anwer; Atta ur Rehman Khan (Journal of Plant Pathology, 2023)

3D graphene-based material: Overview, perspective, advancement, energy storage, biomedical engineering and environmental applications a bibliometric analysis - Ehtisham Umar; Muhammad Ikram; Junaid Haider; Walid Nabgan; Muhammad Imran; Ghazanfar Nazir (Journal of Environmental Chemical Engineering, 2023)

Sn-doped nanoconfinements of SBA-15 for oxidative desulfurization: Kinetics and thermodynamics - Mateen Ahmad; Sobia Aslam; Fazle Subhan; Liu Zhen; Zifeng Yan; Muhammad Yaseen; Muhammad Ikram; Afaq Nazir (Fuel, 2023)

Isolation of Endophytic Fungi from Halophytic Plants and their Identification and Screening for Auxin Production and Other Plant Growth Promoting Traits - Muhammad Ikram; Niaz Ali; Gul Jan; Farzana Gul Jan; Rainaz Pervez; Muhammad Romman; Rimsha Zainab; Humaira Yasmin; Naeem Khan (Journal of Plant Growth Regulation, 2023)

Anti-inflammatory mechanisms of eucalyptol rich Eucalyptus globulus essential oil alone and in combination with flurbiprofen - Bushra Arooj; Sajid Asghar; Mohammad Saleem; Syed Haroon Khalid; Muhammad Asif; Tahir Chohan; Ikram Ullah Khan; Hafiz Muhammad Zubair; Hafiza Sidra Yaseen (Inflammopharmacology, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Efficient resource utilization of the electricity distribution sector using nonparametric data envelopment analysis and influential factors - Majid Ikram; Muhammad Zahid Rafique; Kamel Si Mohammed; Rida Waheed; Diogo Ferraz (Utilities Policy, 2023)

Polyvinylpyrrolidone and chitosan-coated magnetite (Fe3O4) nanoparticles for catalytic and antimicrobial activity with molecular docking analysis - Ayesha; Muhammad Imran; Ali Haider; Iram Shahzadi; Sawaira Moeen; Anwar Ul-Hamid; Walid Nabgan; Anum Shahzadi; Thamraa Alshahrani; Muhammad Ikram (Journal of Environmental Chemical Engineering, 2023)

Exploiting genetic diversity in enhancing phenotypic plasticity to develop climate-resilient cotton - Zulfiqar Ali; Hira Maryam; Muhammad Abu Bakar Saddique; Rao Muhammad Ikram (Genetic Resources and Crop Evolution, 2023)

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Improving Significant Wave Height Prediction Using a Neuro-Fuzzy Approach and Marine Predators Algorithm - Rana Muhammad Adnan Ikram; Xinyi Cao; Tayeb Sadeghifar; Alban Kuriqi; Ozgur Kisi; Shamsuddin Shahid (Journal of Marine Science and Engineering, 2023)
This study investigates the ability of a new hybrid neuro-fuzzy model by combining the neuro-fuzzy (ANFIS) approach with the marine predators’ algorithm (MPA) in predicting short-term (from 1 h ahead to 1 day ahead) significant wave heights. Data from two stations, Cairns and Palm Beach buoy, were used in assessing the considered methods. The ANFIS-MPA was compared with two other hybrid methods, ANFIS with genetic algorithm (ANFIS-GA) and ANFIS with particle swarm optimization (ANFIS-PSO), in predicting significant wave height for multiple lead times ranging from 1 h to 1 day. The multivariate adaptive regression spline was investigated in deciding the best input for prediction models. The ANFIS-MPA model generally offered better accuracy than the other hybrid models in predicting significant wave height in both stations. It improved the accuracy of ANFIS-PSO and ANFIS-GA by 8.3% and 11.2% in root mean square errors in predicting a 1 h lead time in the test period.

Novel evolutionary-optimized neural network for predicting landslide susceptibility - Rana Muhammad Adnan Ikram; Imran Khan; Hossein Moayedi; Atefeh Ahmadi Dehrashid; Ismail Elkhrachy; Binh Nguyen Le (Environment, Development and Sustainability, 2023)

A novel swarm intelligence: cuckoo optimization algorithm (COA) and SailFish optimizer (SFO) in landslide susceptibility assessment - Rana Muhammad Adnan Ikram; Atefeh Ahmadi Dehrashid; Binqiao Zhang; Zhihuan Chen; Binh Nguyen Le; Hossein Moayedi (Stochastic Environmental Research and Risk Assessment, 2023)

Simulated Grazing (Clipping) Affected Growth and Nutritional Quality of Barley, Rye, and Wheat in an Arid Climate - Irshad Ahmad; Hua Wang; Muhammad Kamran; Khushnuma Ikram; Fujiang Hou (Journal of Plant Growth Regulation, 2023)

3D porous superoleophilic/hydrophobic grapefruit peel aerogel for efficient removal of emulsified-oil from water - Muhammad Imran; Ashraful Islam; Fatima Ismail; Panyue Zhang; Majid Basharat; Muhammad Ikram; Ahmed Uddin; Shah Zeb; Qadeer-Ul Hassan; Yongxiang Gao (Journal of Environmental Chemical Engineering, 2023)

Recyclable Cu–Ag bimetallic nanocatalyst for radical scavenging, dyes removal and antimicrobial applications - Faisal Ali; Sadia Akbar; Mika Sillanpaa; Umer Younas; Adnan Ashraf; Muhammad Pervaiz; Rizwan Kausar; Ikram Ahmad; Asma A. Alothman; Mohamed Ouladsmane (Chemosphere, 2023)

A computationally efficient unscented Kalman smoother for ameliorated tracking of subatomic particles in high energy physics experiments - Jahanzeb Akhtar; Imran Ghous; Muhammad Jawad; Zhaoxia Duan; Ikram Ullah Khosa; Saim Ahmed (Computer Physics Communications, 2023)

Water Temperature Prediction Using Improved Deep Learning Methods through Reptile Search Algorithm and Weighted Mean of Vectors Optimizer - Rana Muhammad Adnan Ikram; Reham R. Mostafa; Zhihuan Chen; Kulwinder Singh Parmar; Ozgur Kisi; Mohammad Zounemat-Kermani (Journal of Marine Science and Engineering, 2023)
Precise estimation of water temperature plays a key role in environmental impact assessment, aquatic ecosystems’ management and water resources planning and management. In the current study, convolutional neural networks (CNN) and long short-term memory (LSTM) network-based deep learning models were examined to estimate daily water temperatures of the Bailong River in China. Two novel optimization algorithms, namely the reptile search algorithm (RSA) and weighted mean of vectors optimizer (INFO), were integrated with both deep learning models to enhance their prediction performance. To evaluate the prediction accuracy of the implemented models, four statistical indicators, i.e., the root mean square errors (RMSE), mean absolute errors, determination coefficient and Nash–Sutcliffe efficiency were utilized on the basis of different input combinations involving air temperature, streamflow, precipitation, sediment flows and day of the year (DOY) parameters. It was found that the LSTM-INFO model with DOY input outperformed the other competing models by considerably reducing the errors of RMSE and MAE in predicting daily water temperature.

Nerium oleander could be used for sustainable management of traffic-borne elemental-enriched roadside soils - Noreen Khalid; Ali Noman; Atia Nazir; Aasma Tufail; Naila Hadayat; Fahad Mohammed Alzuaibr; Sobia Ikram; Noreen Akhter; Mumtaz Hussain; Muhammad Aqeel (Environmental Science and Pollution Research, 2023)

Health impacts from TRAPs and carbon emissions in the projected electric vehicle growth and energy generation mix scenarios in Malaysia - Soo Chen Kwan; Sazalina binti Zakaria; Mohd Faiz Ibrahim; Wan Rozita Wan Mahiyuddin; Nurzawani Md Sofwan; Muhammad Ikram A Wahab; Radin Diana R. Ahmad; Ahmad Rosly Abbas; Wei Kian Woon; Mazrura Sahani (Environmental Research, 2023)

Characterization and implication of microplastics on riverine population of the River Ravi, Lahore, Pakistan - Muhammad Haris Raza; Farhat Jabeen; Salma Ikram; Saba Zafar (Environmental Science and Pollution Research, 2023)

Advanced triboelectric nanogenerator-driven drug delivery systems for targeted therapies - Muhammad Ikram; M. A. Parvez Mahmud (Drug Delivery and Translational Research, 2023)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Waste management and green technology: future trends in circular economy leading towards environmental sustainability - Muhammad Tanveer; Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Jawad Sajid; Ikram Ul Haq (Environmental Science and Pollution Research, 2022)

Mechanisms of β-adrenergic receptors agonists in mediating pro and anti-apoptotic pathways in hyperglycemic Müller cells - Sher Zaman Safi; Laiba Saeed; Humaira Shah; Zahina Latif; Abid Ali; Muhammad Imran; Nawshad Muhammad; Talha Bin Emran; Vetriselvan Subramaniyan; Ikram Shah Bin Ismail (Molecular Biology Reports, 2022)

Effects of ash derived from livestock manure and two other treatments on soil moisture content and water infiltration rate - Fatemehsadat Mortazavizadeh; Amirali Fatahi; Keyvan Asefpour Vakilian; Paulo H. Pagliari; Artemi Cerdà; Majid Mirzaei; Xiuju Zhang; Rana Muhammad Adnan Ikram (Irrigation and Drainage, 2022)
This study investigates the effects of using livestock manure (LM), livestock manure ash (LMA) and the combination of LM with LMA (LM + LMA) on the soil moisture content and water infiltration rate of clay, clay loam and sandy loam soils. The soil moisture content and water infiltration rate were 11.60, 8.90 and 6.85% and 1.98, 1.55 and 1.62 cm h‾¹ for clay, clay loam and sandy loam soils, respectively, by the application of 15 t ha‾¹ LM. Moreover, using 15 t ha‾¹ of LMA had the most desirable effects on the soil moisture content in the clay and clay loam soils. Using this treatment, the soil moisture content and water infiltration rate were 10.85, 11.20 and 7.24% and 2.40, 1.90 and 1.75 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Promising results were obtained using 15 + 15 t ha‾¹ of LM + LMA, where the soil moisture content and water infiltration rate were 11.50, 10.20 and 8.20% and 2.80, 1.90 and 1.72 cm h‾¹ for clay, clay loam and sandy loam soils, respectively. Both LMA and its combination with LM were found to be positive strategies to achieve sustainable agricultural goals because of the increased water infiltrates (less runoff) available for the plants.

Antidiarrheal and antispasmodic activities of Trillium govanianum rhizomes extract: involvement of calcium channel blockade - Naveed Muhammad; Shafiq Ur Rahman; Hilal Uddin; Omer Shehzad; Muhammad Ismail; Niaz Ali; Aslam Khan; Muhammad Shahid; Abid Ullah; Shujaat Ahmad; Haya Hussain; Ikram ul Haq; et al. (Natural Product Research, 2022)

Correction to: Sustainable supply chain management and green technologies: a bibliometric review of literature - Zhang Yu; Muhammad Waqas; Muhammad Tabish; Muhammad Tanveer; Ikram Ul Haq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Sustainable supply chain management and green technologies: a bibliometric review of literature - Zhang Yu; Muhammad Waqas; Muhammad Tabish; Muhammad Tanveer; Ikram Ul Haq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Sustainable economic activities, climate change, and carbon risk: an international evidence - Muhammad Kamran Khan; Hai Hong Trinh; Ikram Ullah Khan; Subhan Ullah (Environment, Development and Sustainability, 2022)

Genome-wide identification and development of InDel markers in tobacco (Nicotiana tabacum L.) using RAD-seq - Haiyang Li; Muhammad Ikram; Yanshi Xia; Ronghua Li; Qinghua Yuan; Weicai Zhao; Kadambot H. M. Siddique; Peiguo Guo (Physiology and Molecular Biology of Plants, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Sub-lethal effects of organophosphates and synthetic pyrethroid insecticides on muscle tissue transaminases of Oreochromis niloticus in vivo - Muhammad Amin; Masarrat Yousuf; Naveed Ahmad; Mohammad Attaullah; Muhammad Ikram; Attia A. Abou Zaid; Clement Ameh Yaro; Eida M. Alshammari; Yaser S. Binnaser; Gaber El-Saber Batiha; Islam Dad Buneri (Toxicological Research, 2022)

Green growth and sustainable development: dynamic linkage between technological innovation, ISO 14001, and environmental challenges - Nabila Abid; Federica Ceci; Muhammad Ikram (Environmental Science and Pollution Research, 2022)

Does economic complexity matter for environmental sustainability? Using ecological footprint as an indicator - Muhammad Zahid Rafique; Abdul Majeed Nadeem; Wanjun Xia; Majid Ikram; Hafiz Muhammad Shoaib; Umer Shahzad (Environment, Development and Sustainability, 2022)

Growth prediction of Alternanthera philoxeroides under salt stress by application of artificial neural networking - Qaiser Javed; Ahmad Azeem; Jianfan Sun; Ikram Ullah; Daolin Du; Muhammad Ali Imran; Muhammad Imran Nawaz; Hassan T. Chattha (Plant Biosystems, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Factors affecting managers’ intention to adopt green supply chain management practices: evidence from manufacturing firms in Jordan - Luay Jum’a; Muhammad Ikram; Ziad Alkalha; Maher Alaraj (Environmental Science and Pollution Research, 2022)

Spatial and temporal fluctuation of rainfall and drought in Balochistan province, Pakistan - Muhammad Rafiq; Yue Cong Li; Yanpei Cheng; Ghani Rahman; Ikram Ullah; Ahmad Ali (Arabian Journal of Geosciences, 2022)

Characterization of Exotic, Native and Wild-Type Genotypes of Sugarcane (Saccharum spp. Hybrids) for Internal Nitrogen Use Efficiency Under Different Nitrogen Levels - Muhammad Anas; Krishan K. Verma; Ikram Ul Haq; Muhammad Naeem; Qiang Li; Fen Liao; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2021)

Comparative Effects of Individual and Consortia Plant Growth Promoting Bacteria on Physiological and Enzymatic Mechanisms to Confer Drought Tolerance in Maize (Zea mays L.) - Muhammad Saleem; Fahim Nawaz; Muhammad Baqir Hussain; Rao Muhammad Ikram (Journal of Soil Science and Plant Nutrition, 2021)
Mitigation strategies based on plant–microbe interactions to increase the performance of plants under water-deficit conditions are well documented. However, little is known about a suitable consortium of bacterial inoculants and underlying physiological and enzymatic events to improve drought tolerance in maize. We performed laboratory and pot experiments to understand the synergistic interactions among plant growth-promoting bacteria to alleviate the drought-induced damages in maize. Initially, ten bacterial strains were evaluated for their osmotic stress tolerance capacity by growing them in a media containing 0, 10, 20, and 30% polyethylene glycol (PEG-6000). Also, the seeds of a drought tolerant (NK-6654) and sensitive (SD-626) maize cultivar were inoculated with these bacterial strains in the first pot experiment to determine their effects on the growth and physiological processes. Later, in the second pot experiment, the best performing inoculants were selected to study the individual and synergistic effects of bacterial inoculation to confer drought tolerance in maize. Our findings showed that the inoculation with tolerant strains resulted in higher photosynthetic activity (25–39%), maintenance of leaf water status (14–18%) and pigments (27–32%), and stimulation of antioxidant machinery (28–38%) than no inoculation in water-stressed maize seedlings. Moreover, the treatment with bacteria consortia further stimulated the drought protective mechanisms and resulted in higher efficiency of photosynthetic (47–61%) and antioxidant systems (42–62%) than the individual inoculants under water-deficit conditions. We conclude that the inoculation with microbial consortia regulates water uptake, photosynthetic performance, and stress metabolites to minimize drought-induced damages in maize.

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

Does temperature matter for COVID-19 transmissibility? Evidence across Pakistani provinces - Muhammad Irfan; Muhammad Ikram; Munir Ahmad; Haitao Wu; Yu Hao (Environmental Science and Pollution Research, 2021)

Antioxidative and Anti-inflammatory Effects of Kojic Acid in Aβ-Induced Mouse Model of Alzheimer’s Disease - Amjad Khan; Tae Ju Park; Muhammad Ikram; Sareer Ahmad; Riaz Ahmad; Min Gi Jo; Myeong Ok Kim (Molecular Neurobiology, 2021)

Evaluation of the allelopathic effects of leachate from an invasive species (Wedelia triobata) on its own growth and performance and those of a native congener (W. chinensis) - Muhammad Saif Ullah; Jianfan Sun; Susan Rutherford; Ikram Ullah; Qaiser Javed; Ghulam Rasool; Muhammad Ajmal; Daolin Du (Biological Invasions, 2021)

Silver nanoparticles biosynthesized from secondary metabolite producing marine actinobacteria and evaluation of their biomedical potential - Ashia Alam; Faouzia Tanveer; Ali Talha Khalil; Tanzeel Zohra; Saleh Khamlich; Muhammad Masroor Alam; Muhammad Salman; Muhammad Ali; Aamer Ikram; Zabta Khan Shinwari; Malik Maaza (Antonie van Leeuwenhoek, 2021)

Nitrogen balance, production performance, and plasma metabolites of lactating buffaloes in response to varying dietary protein levels - Muhammad Uzair Akhtar; Hifzulrahman; Muhammad Imran; Talat Naseer Pasha; Anjum Khalique; Muhammad Saadullah; Muhammad Naeem Tahir; Muhammad Ikram-ul-Haq; Muhammad Naveed-ul-Haque (Tropical Animal Health and Production, 2021)

Assessing the physico-chemical parameters and some metals of underground water and associated soil in the arid and semiarid regions of Tank District, Khyber Pakhtunkhwa, Pakistan - Asif Khan; Muhammad Naeem; Muhammad Bilal; Abbas Khan; Fazle Subhan; Muhammad Ikram; Muhammad Ishaq Ali Shah; Saleem Ullah; Asmat Ullah; Atta Ullah (Environmental Monitoring and Assessment, 2021)

The influence of personality traits on sustainability-oriented entrepreneurial intentions: the moderating role of servant leadership - Sajjad Nawaz Khan; Muhammad Mubushar; Ikram Ullah Khan; Hafiz Mudassir Rehman; Safeer Ullah Khan (Environment, Development and Sustainability, 2021)

Expression of DnMTs and MBDs in AlCl3-Induced Neurotoxicity Mouse Model - Muhammad Faisal Ikram; Syeda Mehpara Farhat; Aamra Mahboob; Saeeda Baig; Ahmed Yaqinuddin; Touqeer Ahmed (Biological Trace Element Research, 2021)

Growing green? Sectoral-based prediction of GHG emission in Pakistan: a novel NDGM and doubling time model approach - Erum Rehman; Muhammad Ikram; Shazia Rehman; Ma Tie Feng (Environment, Development and Sustainability, 2021)

Genomic-based characterization of Enterococcus spp.: an emerging pathogen isolated from human gut - Zumara Younus; Sagar M. Goyal; Vikash Singh; Aamer Ikram; Muhammad Imran (Molecular Biology Reports, 2021)

Genetic and expression deregulation of immunoregulatory genes in rheumatoid arthritis - Muhammad Zhaid Hussain; Ishrat Mahjabeen; Muhammad Shahid Khan; Naila Mumtaz; Syed Uzair Maqsood; Farooq Ikram; Syed Nazir Ahmed; Qurrat-ul-Ain Kalim; Rabia Abbas; Ahmed Ammar Cheema (Molecular Biology Reports, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

Optimization, in vitro release and toxicity evaluation of novel pH sensitive itaconic acid-g-poly(acrylamide)/sterculia gum semi-interpenetrating networks - Fauzia Rehman; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Akhtar Rasul; Huma Mahmood; Abid Mehmood Yousaf; Yasser Shahzad; Muhammad Mudassar; Noor Ul Amin Mohsin (DARU Journal of Pharmaceutical Sciences, 2021)

Assessment and prediction of environmental sustainability: novel grey models comparative analysis of China vs. the USA - Muhammad Ikram; Robert Sroufe; Qingyu Zhang; Marcos Ferasso (Environmental Science and Pollution Research, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Investigation of in vivo anti-inflammatory and anti-angiogenic attributes of coumarin-rich ethanolic extract of Melilotus indicus - Mohammad Saleem; Muhammad Asif; Anum Parveen; Hafiza Sidra Yaseen; Malik Saadullah; Asiya Bashir; Jawaria Asif; Mehwish Arif; Ikram Ullah Khan; Rizwan Ullah Khan (Inflammopharmacology, 2021)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Sectoral-based CO2 emissions of Pakistan: a novel Grey Relation Analysis (GRA) approach - Erum Rehman; Muhammad Ikram; Ma Tie Feng; Shazia Rehman (Environmental Science and Pollution Research, 2020)

Evaluation of edible bird’s nest processing plant wastewater quality: a factory case study - Siti Shahara Zulfakar; Farah Natasha Haezam; Mohd Sham Othman; Nur Faizah Abu Bakar; Muhammad Ikram A. Wahab (Arabian Journal of Geosciences, 2020)

Occurrence of heavy metals and pesticide residues in tomato crop: a threat to public health - Muhammad Ishaq; Nighat Sultana; Muhammad Ikram; Amjad Iqbal; Farooq Shah; Muhammad Hamayun; Anwar Hussain (Arabian Journal of Geosciences, 2020)

Salivary Proteomic Analysis of Betel Nut (Areca catechu) Consumers by Mass Spectrometry Revealed Primary Indication of Oral Malignancies - Rabia Sultan; Munazza Raza Mirza; Muhammad Iqbal Choudhary; Mehtab Alam; Ikram-ul Haque (International Journal of Peptide Research and Therapeutics, 2020)

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Natural and semisynthetic polymers blended orodispersible films of citalopram - Yasser Shahzad; Maimoona Maqbool; Talib Hussain; Abid Mehmood Yousaf; Ikram Ullah Khan; Tariq Mahmood; Muhammad Jamshaid (Natural Product Research, 2020)

Genetic association of insulin receptor substrate-1 (IRS-1, rs1801278) gene with insulin resistant of type 2 diabetes mellitus in a Pakistani population - Abdullah Abdo Albegali; Muhammad Shahzad; Saqib Mahmood; Muhammad Ikram Ullah (Molecular Biology Reports, 2019)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Phosphate fertilizer premixing with farmyard manure enhances phosphorus availability in calcareous soil for higher wheat productivity - Wasiq Ikram; Muhammad Akhtar; Christian Morel; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2019)

Integrated effect of energy consumption, economic development, and population growth on CO2 based environmental degradation: a case of transport sector - Muhammad Mohsin; Qaiser Abbas; Jijian Zhang; Muhammad Ikram; Nadeem Iqbal (Environmental Science and Pollution Research, 2019)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

Assessing the solar PV power project site selection in Pakistan: based on AHP-fuzzy VIKOR approach - Yasir Ahmed Solangi; Syed Ahsan Ali Shah; Hashim Zameer; Muhammad Ikram; Burak Omer Saracoglu (Environmental Science and Pollution Research, 2019)

A cross-sectional study of methicillin-resistant Staphylococcus aureus at the equine-human interface - Namra Waqar; Quratulain Amin; Tariq Munir; Muhammad Sohaib Ikram; Naveed Shahzad; Arkim Mirza; Arshad Ali; Muhammad Imran Arshad (Tropical Animal Health and Production, 2019)

Hesperetin Confers Neuroprotection by Regulating Nrf2/TLR4/NF-κB Signaling in an Aβ Mouse Model - Muhammad Ikram; Tahir Muhammad; Shafiq Ur Rehman; Amjad Khan; Min Gi Jo; Tahir Ali; Myeong Ok Kim (Molecular Neurobiology, 2019)

Novel antimicrobial and antioxidative activity by endophytic Penicillium roqueforti and Trichoderma reesei isolated from Solanum surattense - Muhammad Ikram; Niaz Ali; Gul Jan; Muhammad Hamayun; Farzana Gul Jan; Amjad Iqbal (Acta Physiologiae Plantarum, 2019)

Cadmium immobilization in the soil and accumulation by spinach (Spinacia oleracea) depend on biochar types under controlled and field conditions - Muhammad Farooq Qayyum; Rabia Abdur Rehman; Seemab Liaqat; Muhammad Ikram; Shafaqat Ali; Muhammad Rizwan; Muhammad Zia ur Rehman; Muhammad Zafar-ul-Hye; Qaiser Hussain (Arabian Journal of Geosciences, 2019)

Melatonin Rescue Oxidative Stress-Mediated Neuroinflammation/ Neurodegeneration and Memory Impairment in Scopolamine-Induced Amnesia Mice Model - Tahir Muhammad; Tahir Ali; Muhammad Ikram; Amjad Khan; Sayed Ibrar Alam; Myeong Ok Kim (Journal of Neuroimmune Pharmacology, 2019)

Forecasting number of ISO 14001 certifications of selected countries: application of even GM (1,1), DGM, and NDGM models - Muhammad Ikram; Amin Mahmoudi; Syed Zulfiqar Ali Shah; Muhammad Mohsin (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Gintonin Mitigates MPTP-Induced Loss of Nigrostriatal Dopaminergic Neurons and Accumulation of α-Synuclein via the Nrf2/HO-1 Pathway - Min Gi Jo; Muhammad Ikram; Myeung Hoon Jo; Lang Yoo; Kwang Chul Chung; Seung-Yeol Nah; Hongik Hwang; Hyewhon Rhim; Myeong Ok Kim (Molecular Neurobiology, 2019)

Natural Dietary Supplementation of Anthocyanins via PI3K/Akt/Nrf2/HO-1 Pathways Mitigate Oxidative Stress, Neurodegeneration, and Memory Impairment in a Mouse Model of Alzheimer’s Disease - Tahir Ali; Taehyun Kim; Shafiq Ur Rehman; Muhammad Sohail Khan; Faiz Ul Amin; Mehtab Khan; Muhammad Ikram; Myeong Ok Kim (Molecular Neurobiology, 2018)

Spatial-temporal variations in surface ozone over Ushuaia and the Antarctic region: observations from in situ measurements, satellite data, and global models - Mohd Shahrul Mohd Nadzir; Matthew J. Ashfold; Md Firoz Khan; Andrew D. Robinson; Conor Bolas; Mohd Talib Latif; Benjamin M. Wallis; Mohammed Iqbal Mead; Haris Hafizal Abdul Hamid; Neil R. P. Harris; Zamzam Tuah Ahmad Ramly; Goh Thian Lai; et al. (Environmental Science and Pollution Research, 2018)

Correction to: HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Muhammad Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

Hutchinson–Gilford Progeria Syndrome: A Premature Aging Disease - Muhammad Saad Ahmed; Sana Ikram; Nousheen Bibi; Asif Mir (Molecular Neurobiology, 2017)

Characterization of rainwater chemical composition after a Southeast Asia haze event: insight of transboundary pollutant transport during the northeast monsoon - Mohd Shahrul Mohd Nadzir; Chin Yik Lin; Md Firoz Khan; Mohd Talib Latif; Doreena Dominick; Haris Hafizal Abdul Hamid; Noorlin Mohamad; Khairul Nizam Abdul Maulud; Muhammad Ikram Abdul Wahab; Nurul Farahana Kamaludin; Mohamad Azwani Shah Mat Lazim (Environmental Science and Pollution Research, 2017)

Cytotoxic cardiac glycosides from the fruit (pods) of Adenium obesum (Forssk.) Roem. & Schult - Salman Khalid Ahmed; Muhammad Ali Versiani; Ambreen Ikram; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2017)

Determination of Serum Trace Elements (Zn, Cu, and Fe) in Pakistani Patients with Rheumatoid Arthritis - Zia Ullah; Muhammad Ikram Ullah; Shabbir Hussain; Haiba Kaul; Khalid P. Lone (Biological Trace Element Research, 2017)

New dammarane and ursane-type triterpenoids from the flower of Ixora coccinea Linn. - Ambreen Ikram; Muhammad Ali Versiani; Amna Khatoon; Salman Khalid Ahmed; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2016)

Thymoquinone and Vitamin C Attenuates Pentylenetetrazole-Induced Seizures Via Activation of GABAB1 Receptor in Adult Rats Cortex and Hippocampus - Ikram Ullah; Haroon Badshah; Muhammad Imran Naseer; Hae Young Lee; Myeong Ok Kim (NeuroMolecular Medicine, 2015)

Cloning, characterization and molecular docking of a highly thermostable β-1,4-glucosidase from Thermotoga petrophila - Ikram Ul Haq; Mahmood Ali Khan; Bushra Muneer; Zahid Hussain; Sumra Afzal; Sana Majeed; Naeem Rashid; Muhammad Mohsin Javed; Ishtiaq Ahmad (Biotechnology Letters, 2012)

Comprehensive screening and selection of okra (Abelmoschus esculentus) germplasm for salinity tolerance at the seedling stage and during plant ontogeny - Ikram-ul- Haq; Asif Ali Khan; Iqrar Ahmad Khan; Muhammad Abubakkar Azmat (Journal of Zhejiang University-SCIENCE B, 2012)

Protective Function of Nicotinamide Against Ketamine-induced Apoptotic Neurodegeneration in the Infant Rat Brain - Najeeb Ullah; Ikram Ullah; Hae Young Lee; Muhammad Imran Naseer; Park Moon Seok; Jawad Ahmed; Myeong Ok Kim (Journal of Molecular Neuroscience, 2012)

Cloning and expression of β-glucosidase gene from Bacillus licheniformis into E. coli BL 21 (DE3) - Sana Zahoor; Muhammad M. Javed; Muhammad N. Aftab; Ikram-ul-Haq (Biologia, 2011)

Comparative assessment of selenite (SeIV) detoxification to elemental selenium (Se0) by Bacillus sp. - Madiha Ikram; Muhammad Faisal (Biotechnology Letters, 2010)

Insoluble but enzymatically active α-amylase from Bacillus licheniformis - Naeem Rashid; Alia Farooq; Ikram-ul-Haq; Muhammad Akhtar (Biologia, 2009)